The effect of employee satisfaction on employee loyalty at Telekom Malaysia Berhad / Syaidatul Nadiah Hasan - Hasan, Syaidatul Nadiah (2012)
On the successful history in many recent year, TM also have problem regarding with their employees in term of resignation, termination, welfare, turnover, and others. For the largest company in Malaysia, they need to retain and make the employees satisfy and also make them to stay and loyal to the company. The issue of satisfaction and loyalty are the elements that very important to the company. So, in this study is about to know the employee satisfaction level which consists of three variables that are satisfaction from recognition and rewards, satisfaction from working conditions and also satisfaction from relationship with supervisor that impact to the employee loyalty. Besides that, the main aims in this survey is to determine those independent variables: satisfaction from recognition and rewards, satisfaction from working conditions and also satisfaction from relationship with supervisor effect to the employee loyalty which is as a dependent variable in this study and also to study the correlation. Numerous researches indicate that employee satisfaction is positively related to employee loyalty to their companies (Brown and Peterson, 1993; Griffeth et al, 2000; Hom and Kinicki, 2001). Moreover, Jawahar (2006) also found that employee satisfaction has a linkage with employee loyalty. Besides that, this study also needs to see the relationship between employee satisfactions and employee loyalty.